Preparation of conductive and flame-retardant pu/go/dopo printed films - BİRTANE, HATİCE (My University, 2022)
© 2022 Authors.Printed electronics are emerging technology products that we use in every moment of our daily lives. It is used in many fields from health, textile, electronics to communication. Inks with nanometal or organic content can be used in printed electronics. The ability of printed electronics to withstand temperature makes its use widespread in the electronics industry. Main aim of the study is to combine surface modified graphene oxide-based conductive inks with flame retardant materials. In this study, an effective and simple approach for the preparation of polyurethane acrylate (PUA) screen printing ink containing surface modified reduced graphene oxide (rGO) which has flame retardant activity. A new and effective flame-retardant additive; 9,10-dihydro-9,10-oxa-10-phosphaphenanthrene-10-oxide (DOPO), silane coupling agent and reduced graphene oxide was synthesized. In this synthesis, first reduced graphene oxide was modified with (methacryloyloxy)propyltrimethoxysilane, and then reacted with DOPO to obtain a flame-retardant monomer containing P and Si. Based on the successful modification reactions, screen-printing ink containing polyurethane acrylate and different amounts of modified graphene oxide content (0, 5 and 10 wt%) were prepared and screen printed on the paper surface. In addition, coatings were made on the paper surface to determine some the properties. LOI values, thermal properties, contact angle values, conductivity and surface properties of the obtained prints and coatings films were investigated. As a result, conductive screen-printing ink resistant to high temperatures was successfully produced and printed coatings and free films were formed.
Keywords: Bilgisayar Bilimleri; Bilgisayar Grafiği; Mühendislik ve Teknoloji; Computer Sciences; Computer Graphics; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Bilgisayar Bilimi; BİLGİSAYAR BİLİMİ, İNTERDİSİPLİNER UYGULAMALAR; Engineering, Computing & Technology (ENG); COMPUTER SCIENCE; COMPUTER SCIENCE, INTERDISCIPLINARY APPLICATIONS; Bilgisayar Grafikleri ve Bilgisayar Destekli Tasarım; Fizik Bilimleri; Bilgisayar Bilimi Uygulamaları; Computer Graphics and Computer-Aided Design; Physical Sciences; Computer Science Applications; flame retardant; polyurethane acrylate coating; printed electronics; reduced graphene oxide; UV curable coating